Avaliação do uso do pensamento estatístico e técnicas estatísticas em empresas de bens de capital seriados do Estado de São Paulo - Carvalho, Nelio Garbellini de (Universidade Federal de São Carlos, 2015)
With more advanced marketing relations, various changes are taking place in regard to competitive factor markets, among which, the importance of quality processes and goods supplied to the society, stand out. Therefore, diverse programs and methods have been developed to monitor indicators of production processes and the characteristics of roduct quality, many of which are supported by statistical concepts. This process encourages understanding and the use of Statistical Thinking (ST), Statistical Engineering (SE), and Statistical Techniques (STe) in businesses, highlighting their importance to quality management and the efficiency of organizational processes. This thesis’s aim was to analyze the use of ST and STe in a sample of industries in the sector of serial capital goods located in the state of São Paulo, Brazil. For that, an exploratory-descriptive survey was conducted with 42 medium and large companies from different segments of the sector. Data were statistically analyzed using descriptive and multivariate methods (cluster analysis, association and correlation). These analyses revealed there is considerable space to diffuse Statistical Thinking and Statistical Techniques in these companies, as well as revealed a lack of training in statistical principles and techniques, the main obstacles to the systematic application of these techniques, and the lack of support on the part of top management. There is evidence that the successful implementation of Total Quality Management (TQM) and Total Productive Maintenance in the industries of sector significantly influences the diffusion of ST and the application of STe; while the use of Six Sigma program especially impacts the application of more complex STe; and ST has the potential to promote the application of STe.
Keywords: Pensamento estatístico; Engenharia estatística; Técnicas estatísticas; Indústria de bens de capital seriados; Statistical thinking; Statistical engineering; Statistical techniques; Serial capital goods sector; ENGENHARIAS::ENGENHARIA DE PRODUCAO